Characteristic of bubble rise in quiescent or moving liquids - Noor Aini Mohamed Rafi (Nanyang Technological University, 2020)
An experimental study was conducted to investigate the effects of varying bubble sizes and different fluid properties (density and viscosity) on the rising behaviour of a bubble, such as its velocity. Three dumping cups with different diameters of were used to mould and shape the size of the bubbles. Three different fluids, namely, water, water-glycerol mixture (50%-50% by volume), and glycerol, were used to explore how the bubbles adapted to the different fluid properties. To analyse the experimental results, a ‘Tracker’ software and ‘Kinovea’ software were used as they provided the necessary tools such as, tracking the bubbles at each frame throughout their trajectory to the surface. Tracking the bubbles’ centre of mass was essential in determining its change in velocity at and size at every frame as it surfaced. From the result analysis, it was concluded that the varying bubble sizes and the different types of fluids have a significant impact on the velocity and mobility of the bubbles. Bigger bubbles had larger average velocities due to a greater buoyancy force, and glycerol, the densest fluid among the three test fluids, resulted in bubbles having a lower average velocity, due to a larger drag force. The effects of bubble size and fluid type were evident in concluding the average velocities of the bubbles. It can be concluded that a smaller bubble in a denser fluid will have a larger average velocity. Other than velocities, the change in shape of the bubbles were also analysed.